Discovery-centered versus teacher-centered patterns of instruction changes in critical thinking - Ramos, Herminia Cruz 1932- (s.n.], 1971)
This investigation was conducted to seek supporting evidence to the hypothesis that instructional method does affect the pupils' ability to think critically and vice versa. The primary purpose of this investigation was to find the difference in change, if there is, in the critical thinking ability between pupils taught in the discovery-centered and those in teacher-centered patterns of instruction in grade six science.